Vision Research Literature May Not Represent the Full Intellectual Range of Autism Spectrum Disorder - Brown, Alyse C.; Chouinard, Philippe A.; Crewther, Sheila G. (Frontiers in Human Neuroscience, 2017)
Sensory, in particular visual processing is recognized as often perturbed in individuals with Autism Spectrum Disorder (ASD). However, in terms of the literature pertaining to visual processing, individuals in the normal intelligence range (IQ = 90-110) and above, are more frequently represented in study samples than individuals who score below normal in the border-line intellectual disability (ID) (IQ = 71-85) to ID (IQ < 70) ranges. This raises concerns as to whether or not current research is generalizable to a disorder that is often co-morbid with ID. Thus, the aim of this review is to better understand to what extent the current ASD visual processing literature is representative of the entire ASD population as either diagnosed or recognised under DSM-5. Our recalculation of ASD prevalence figures, using the criteria of DSM-5, indicates approximately 40% of the ASD population are likely to be ID although searching of the visual processing literature in ASD up to July 2016 showed that only 20% of papers included the ASD with-ID population. In the published literature, the mean IQ sampled was found to be 104, with about 80% of studies sampling from the 96-115 of the IQ range, highlighting the marked under-representation of the ID and border-line ID sections of the ASD population. We conclude that current understanding of visual processing and perception in ASD is not based on the mean IQ profile of the DSM-5 defined ASD population that now appears to lie within the border-line ID to ID range. Give the importance of the roll of vision for the social and cognitive processing in ASD, we recommend accurately representing ASD via greater inclusion of individuals with IQ below 80, and into the ID range, in future ASD research.